The decolonial turn: reference lists in PhD theses as markers of theoretical shift/stasis in media and journalism studies at selected South African universities. (8th September 2021) - Mugari, Zvenyika Eckson
Abstract : page_1 other The supervision and production of a PhD thesis often presents a potentially interesting tension between PhDs as conforming to disciplinary epistemologies and PhDs as breaking epistemological boundaries. No academic discipline has been left untouched by decolonial thinking in the South African university space since the eruption of radicalized student protest movements in 2015. The Rhodes Must Fall student protest movement, which quickly morphed into Fees Must Fall, precipitated a new urgency to decolonize the university curriculum in post-apartheid South Africa. A new interdisciplinary conversation in the humanities and social sciences began to emerge which challenged established orthodoxies in favour of de-Westernizing, decolonizing and re-mooring epistemological and pedagogic practices away from Eurocentrism. Whether and how that theoretical ferment filtered into postgraduate students' theses, however, remains to be established. This article deploys a decolonial theoretical framework to explore the tension between epistemic conformity and boundary transgressing in journalism studies by analysing reference lists of PhD theses submitted at three South African Universities three years after the protest movement Rhodes Must Fall. With specific focus on media and journalism studies as a discipline, this article argues that the PhD process represents a site for potential epistemic disobedience and disciplinary border-jumping, and for challenging the canonical insularity of Western theory in journalism studies. The findings appear to disconfirm the thesis that decolonial rhetoric has had a material influence so far on the media studies curriculum, as reflected in reference lists of cited works in their dissertations.